Blackbird [videorecording (DVD)] - Torpe, Christian, 1978-; Sarandon, Susan, 1946-; Winslet, Kate; Wasikowska, Mia, 1989-; Neill, Sam; Duncan, Lindsay; Wilson, Rainn, 1966-; Taylor-Klaus, Bex, 1994-; Boon, Anson; Eley, Mike; Collin, Dinah; Gregson, Peter (Screen Media, 2020)
Lily and Paul summon their loved ones to their country house for one final gathering after Lily decides to end her life on her terms after a long battle with ALS. The couple is planning a loving weekend complete with holiday traditions, but the mood becomes strained when unresolved issues surface between Lily's daughters Jennifer and Anna. Joining the collective farewell is Lily's son in law, her lifelong friend, daughter's partner, and grandson.